RELIGION IN THE MODERN RUSSIAN EDUCATIONAL SPACE: GENESIS, PROBLEMS, PROSPECTS - Pigoreva, Olga (Revista Inclusiones, 2020)
The article analyzes the experience accumulated in Russia in the 1990s and 2010s on organizing the study of religion in a secular school. The author substantiates the relevance of addressing the topic of the presence of knowledge of religion in the modern educational space and the need to study international and Russian practice of teaching knowledge of religion. The genesis of knowledge about religion in Russian schools that have survived a long period of dominance of atheistic ideology is revealed, the importance of regional initiative in the formation of religious education courses is shown. Conclusions about the appropriateness of using the most frequently declared approaches to the study of religion in the future are made taking into account the most frequently expressed provisions of the ongoing discussion on methodological and conceptual approaches to the study of religion, methodological, personnel, legal support and the critical discourse existing in the scientific field regarding the situation in Russia